2018
DOI: 10.7717/peerj.5192
|View full text |Cite
|
Sign up to set email alerts
|

High expression of SLC26A6 in the kidney may contribute to renal calcification via an SLC26A6-dependent mechanism

Abstract: BackgroundSolute-linked carrier 26 gene family 6 (SLC26A6), which is mainly expressed in intestines and kidneys, is a multifunctional anion transporter crucial in the transport of oxalate anions. This study aimed to investigate the role of kidney SLC26A6 in urolithiasis.MethodsPatients were divided into two groups: stone formers and nonstone formers. Samples were collected from patients following nephrectomy. Lentivirus with Slc26a6 (lentivirus-Slc26a6) sequence and lentivirus with siRNA-Slc26a6 (lentivirus-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…These results clearly indicated that there was a renal effect for the compensatory elimination of plasma oxalate if there was a deficiency in the intestinal oxalate secretions. Increased renal Slc26a6 expression contributes to hyperoxaluria [ 30 ]. Our results showed consistent results for a significant increase in Slc26a6 expression not only in the EG kidneys but also in the SB+EG kidneys ( Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%
“…These results clearly indicated that there was a renal effect for the compensatory elimination of plasma oxalate if there was a deficiency in the intestinal oxalate secretions. Increased renal Slc26a6 expression contributes to hyperoxaluria [ 30 ]. Our results showed consistent results for a significant increase in Slc26a6 expression not only in the EG kidneys but also in the SB+EG kidneys ( Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%
“…The Slc26a6 sequence (gene ID: 301010) was chosen according to the National Center for Biotechnology Information (NCBI) GenBank. To knock down Slc26a6 expression, lentiviral vector piLenti-siRNA-red fluorescent protein- (RFP-) based short hairpin RNA (shRNA) against Slc26a6 was constructed, and the targeting sequence of shSlc26a6 was 5′-GGGAACTACTCAAGCTAAT-3′ [ 17 ]. The sequences with red fluorescent protein (RFP) were synthesized and inserted into the vector pWSLV and pilentivirus as pWSLV-05-Slc26a6 and piLenti-siRNA (Slc26a6), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Solute carrier family 26 member 6 (Slc26a6) is an important protein that mediates oxalate transport, and it is expressed mainly in the apical membrane of the intestine and kidneys. In the intestine, Slc26a6 on the apical membrane of intestinal epithelial cells can transport Ox 2− from the blood to the intestinal lumen (oxalate secretion) through Cl/Ox 2− exchange [ 17 ]. In the kidneys, Slc26a6 is located in the proximal tubular epithelial cell side of the renal tubular cell and can transfer oxalate from the blood to the urine through the Cl − /Ox 2− exchange (oxalate secretion) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As Slc26A6-null mice have been reported to be hyperoxaluric and to develop calcium oxalate kidney stones, SLC26A6, which encodes an oxalate transporter, was investigated in a casecontrol study 161,163 . The case-control study identified a SLC26A6 variant to be associated with kidney stone disease 161 , and this variant paradoxically was associated with increased SLC26A6 expression in the kidneys of stone-forming patients 164 . Case control studies have also identified that a TRPV6 haplotype might] increase the risk of absorptive hypercalciuria via increased permeability of the TRPV6 calcium channel 162 .…”
Section: [H2] Genome-wide Association Studiesmentioning
confidence: 99%